Comparative analysis of Desarda and Lichtenstein Inguinal Hernia Repair Techniques - Muhammad Hamza Rana; Ahmed Shafiq; Muhammad Sarim Khan; Zakariya Rasheed; Sardar Ashraf; Sarwat Bibi (Shalamar Medical & Dental College, Lahore, Pakistan, 2024)
Background: Inguinal hernia repair is the most commonly done procedure on the surgical floor these days. Objective: The study aims to evaluate and compare two different inguinal hernia repair techniques in terms of preoperative and postoperative measures. Methods: A comparative cross-sectional study was conducted in the department of Surgery, Aziz Fatimah Hospital from June 27, 2021, to March 02, 2022, using a consecutive sampling non-probability sampling technique. The demographic profile and characteristics of the hernia along with per operative and post-operative variables were collected and analyzed in SPSS 25 using the independent t-test. Results: The patients admitted for the elective inguinal hernia procedure in the ward underwent two routinely done surgical procedures. The mean age of the study population was 37±11 years. The mean age and standard deviation of patients in Group A (Desarda repair) were 36.43±11.01 years and 37.43±11.05 years of patients in Group B (Lichtenstein repair). Less mean operative time and days to return to daily life activities were seen in Group A (Desarda repair) patients compared to Group B (Lichtenstein repair) patients. Moreover, the estimated cost of the Desarda operative procedure was also much less compared to the Lichtenstein repair. Conclusion: The inguinal hernia repair technique Desarda is considered to be more effective and economical than the Lichtenstein repair in terms of per-operative and post-operative measures with less mean operative time, early return to normal activities, and cost-effectiveness.